2009
DOI: 10.1096/fj.09-132019
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of the secretory vesicle proteins IA‐2 and IA‐2β disrupts circadian rhythms of cardiovascular and physical activity

Abstract: Targeted deletion of IA-2 and IA-2beta, major autoantigens in type 1 diabetes and transmembrane secretory vesicle proteins, results in impaired secretion of hormones and neurotransmitters. In the present study, we evaluated the effect of these deletions on daily rhythms in blood pressure, heart rate, core body temperature, and spontaneous physical and neuronal activity. We found that deletion of both IA-2 and IA-2beta profoundly disrupts the usual diurnal variation of each of these parameters, whereas the dele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
28
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 28 publications
4
28
0
Order By: Relevance
“…Most notably in this context, loss of behavioral and physiological rhythms occurs only in mice with disruption of both genes (21). The single-KO mice have, at most, a subtle circadian phenotype (21).…”
Section: Peripheral Gene Expression Rhythms Are Relatively Unaffectedmentioning
confidence: 99%
See 3 more Smart Citations
“…Most notably in this context, loss of behavioral and physiological rhythms occurs only in mice with disruption of both genes (21). The single-KO mice have, at most, a subtle circadian phenotype (21).…”
Section: Peripheral Gene Expression Rhythms Are Relatively Unaffectedmentioning
confidence: 99%
“…A recent study to assess the cardiovascular impact of targeted disruption of IA-2 and IA-2␤ revealed that mice lacking these proteins did not have daily rhythms in blood pressure, heart rate, core body temperature, or spontaneous locomotor activity (21). Electrophysiological studies on the suprachiasmatic nuclei (SCN), the site of the brain's master circadian oscillator, showed that disruption of both IA-2 and IA-2␤ results in significant alterations in neuronal firing rhythms in the SCN (21).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Studies using genetic knockout mouse models have shown the involvement of IA-2 PTPs in secretory functions of pancreatic β-cells, the anterior pituitary, and learningrelated or circadian rhythm-related neuroendocrine cells (Kubosaki et al 2006;Mziaut et al 2008;Kim SM et al 2009;Nishimura et al 2009;Cai et al 2011). Recent molecular and cellular analyses have suggested that the IA-2 family of PTPs specifically contributes to exocytosis of SGs, SG stability, hormone sorting into SGs, and pancreatic β-cell growth Trajkovski et al 2008;Torii et al 2009;Saito et al 2011;Cai et al 2011).…”
mentioning
confidence: 99%